First Observations of Seasonal Variability in Water Mass Properties Across the Agulhas Current. Issue 9 (9th September 2022) - Braby, Laura; Deshayes, Julie; Beal, Lisa; Morris, Tamaryn; Novelli, Guillaume; Maitland, James; Ansorge, Isabelle; Hermes, Juliet
Abstract: The seasonal variability of Agulhas Current properties is not well understood because there have been few data collected during austral winter. Here we analyze 8 repeat hydrographic sections that have been collected across the Agulhas Current at 34°S over the past decade, including the first full‐depth winter surveys of the Agulhas Current, collected in 2016 and 2018. Several differences between the summer and winter occupations of the current are observed which can be attributed to seasonal variability. The most significant difference is the upward shoaling of central waters onto the continental shelf in the summer. These waters flood the shelf with nutrients and oxygen during the summer months, when the Agulhas Current is strongest, but not during winter. Over the top 100 m of the water column seasonality is dominated by surface fluxes, with warmer waters in summer. Immediately below the surface, however, waters are warmer during winter because of the mixing down of Tropical Surface Waters into the deepening mixed layer. Throughout the Agulhas Current at central and intermediate depths waters are cooler in summer and this is due to the upward tilt of the isopycnals, consistent with stronger geostrophic transport. Seasonality is also evident at depth, where North Atlantic Deep Water has a stronger equatorward flow during winter when the Agulhas Current is weaker and shallower. Plain Language Summary: Seasonal changes in temperature and salinity across the Agulhas Current are not well understood because there have been limited hydrographic data collected in this region during winter. In this study, we use a decade worth of observations over the same transect of the Agulhas Current at 34°S, including the first two full‐depth winter surveys of the Agulhas Current, to investigate any changes in the water masses properties from one season to another. In summer, when the Agulhas Current is stronger, nutrient‐rich water masses located offshore and at depth are observed to migrate upward onto the continental shelf, a phenomenon that is not apparent during winter. The upper part of the Agulhas Current is influenced by surface fluxes, with warmer temperatures occurring during summer. Below the surface layer, Agulhas Current temperatures are cooler during summer as a result of the upward tilt of the density surfaces in association with the stronger current. In winter, when the Agulhas Current is relatively weaker and shallower than in summer, we observe more equatorward flow of the deepest water mass, that is North Atlantic Deep Water. Key Points: Nutrient‐rich central waters upwell onto the continental shelf during summer, when the Agulhas Current is stronger, and not during winter Below the seasonal surface layer, waters in the Agulhas Current are cooler during summer due to the upward tilt of isopycnals More equatorward flow of North Atlantic Deep Water is observed in winter, when the Agulhas Current is comparatively shallow and weak